Growth and Technological Quality Indicators of Common Carp in Cages in the Fergana Valley of Uzbekistan - O. T., Esonaliyeva (American Journal of Biodiversity, 2025)
In Spring 2025, common carp (Cyprinus carpio) yearlings were stocked in three floating cages (1 m³ each) installed in the Karkidon Reservoir. The initial total weight of yearlings was 28.9 g on average. They were fed with on-farm-made feed with an estimated protein content of 35%. The feeding ratio was 1.5% of the fish biomass in May and September and 3% throughout the summer. The total catch was conducted on September 30. The fish grew to an average weight of 954 g. The technological quality indicators of commercial carp were analyzed. The indices of the head, carcass, and other organs as a percentage of the total body weight, as well as an organoleptic assessment, are presented. A positive correlation was found between the viscera and gonad weight indices and the total body weight, and a negative correlation between the head weight index and the total body weight of carp of the generation.